2014
DOI: 10.1179/1743278214y.0000000163
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric corrosion of Mg–rare earth alloy in typical inland and marine environments

Abstract: The atmospheric corrosion behaviour of peak aged Mg-5Y-7Gd-1Nd-0?5Zr alloys in typical land (Beijing) and marine (Qingdao) environments were investigated by optical microscopy, SEM and X-ray diffraction. The weight loss rates and residual mechanical properties were analysed. The atmospheric corrosion rates of specimens in a typical marine environment were higher than those in land environment. The results demonstrated that temperature, relative humidity and inorganic salts at field exposed sites played an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Figures 3,[5][6][7] show that the corrosion rates of pure Mg and Mg alloys in the field exposure tests were in the same…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Figures 3,[5][6][7] show that the corrosion rates of pure Mg and Mg alloys in the field exposure tests were in the same…”
mentioning
confidence: 80%
“…Inorganic salt particles in the air might also play an important role in the marine atmospheric corrosion of Mg through modifying the constituents of the liquid film or prolonging the time of the liquid film covering the surface. It is reported that the presence of inorganic salt particles reduces the critical RH required for the formation of a liquid film on the surface [7,8,10,16]. The existence of salt particles promotes the condensation of water vapour in the air to form a thick liquid electrolyte film on the Mg surface.…”
Section: Influence Of T Rh and Saltsmentioning
confidence: 99%
“…In empirical and theoretical practices, corrosion damage modeling and the effect of several field scenarios are related to SCC analysis, where the operating pipelines exposed to different external variables (types of electrolytes, temperature, pH, among other data) have been studied and reported in the literature [ 20 , 168 , 183 , 184 , 185 , 186 , 187 , 188 ]. Nowadays, SCC of carbon steel pipelines is increasing in popularity, and the original mechanical properties of the steels and their initial electrochemical interactions with natural soils, representative soil solutions, or any solution promoting cracking have been described including SCC, intergranular-SCC (IG-SCC), transgranular-SCC (TG-SCC), SSC, HIC, hydrogen embrittlement from testing and characterization of carbon steels in hydrogen or sour testing [ 8 , 9 , 10 , 11 , 189 ].…”
Section: Parameters Reported In the Literature Regarding The Extermentioning
confidence: 99%
“…Common solutions to this are cathodic protection, coatings, and chemical treatment applications. The negative effects of the phenomena of external SCC on carbon steel pipelines could be influenced by the hydrogen generated during cathodic protection, prepared soil solutions, carbonates and bicarbonate solutions as well as the hydrogen that originate from the sulfide compounds, HIC from acidic soils, acidic atmospheric compounds, organic acids, external bacteria induced corrosion, among other external solution promoting cracking [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Oxygen and hydrogen that comes from the low and high (overprotection) cathodic protection, respectively, becoming negative effects for external SCC [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the immersion test was completed in 3.5% NaCl solution for 72 h. Each sample had three replicate samples to ensure the reliability of the results. After the immersion test, the boiling of chromic acid (20% chromium trioxide + 1% silver nitrate) was applied at 100 • C to remove the corrosion products on the surface of the Mg-7Y-1.5Nd alloy samples [26,27]. The samples without corrosion products were successively washed with deionized water and ethyl alcohol.…”
Section: Corrosion and Electrochemical Testsmentioning
confidence: 99%